Sea-level rise and anthropogenic activities recorded in the late Pleistocene/Holocene sedimentary infill of the Guadiana Estuary (SW Iberia) - Delgado, J. (2013)
This study reviews data on sea-level rise during the last 13000 yr cal. BP (13 kyr) as recorded in the estuarine sediments of the Guadiana River (SE Portugal, SW Spain). We combined new data from a 63 m-long borehole, drilled through the entire postglacial sedimentary sequence, with information on five previously studied cores. By integrating sedimentological, geochemical and palaeontological proxies, we were able to make a palaeoenvironmental reconstruction of the Guadiana terminal palaeovalley during the last 13 kyr and propose a curve of sea-level rise for the SW Iberian Atlantic margin. Our foraminifera-based palaeoecological reconstruction, anchored to a 14C age model, reveals rapid sea-level rise from 13 kyr, interrupted during the Younger Dryas and resuming ca 11.5 kyr. The pace of marine transgression slackened ca. 7.5 kyr and since then has progressed upwards at a rate of 1.2 mm yr 1. HoloceneeAnthropocene sediments from two boreholes were also analysed to assess the timing, levels and sources of trace metals produced by acid mine drainage from the Iberian Pyrite Belt. Study of metal/aluminium ratios through the profiles allowed background metal concentrations to be estimated from lithostratigraphic units older than ca. 5 kyr (i.e. unaffected by anthropogenic activities). Human activities are especially evident from 4.5 kyr (the beginning of the Copper Age), with anthropogenic sources of metal fluxes prevailing over natural sources (especially Pb, Co, Ni, and Mn, and, to a lesser extent, Zn, Cu, and Ni). Mining activities became particularly intensive between the late Bronze Age and the Roman period (3e1.5 kyr), when the highest metal enrichment factors were recorded: EFPb z 2, EFCd > 10, EFCr z 2, EFCu z 3, EFZn ¼ 1.4.This study reveals the utility of postglacial sedimentary records for reconstructing historical changes in regional water-sediment quality and separating natural and anthropogenic sources of geochemical contaminants.